ANTIPLAQUE EFFICACY OF GANODERMA LUCIDUM TOOTHPASTE - AN IN VITRO STUDY - S, Prabhjeet; A K, Meena; M, Jesil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the efficacy of Ganoderma lucidum toothpaste as an antiplaque agent and to compare its efficacy with herbal toothpaste and mouthwash. Methods: Pooled saliva was collected in a sterile container from the volunteers after taking the consent. Tissue culture plate with 12 (3 Ã— 4) wells was chosen. Pooled saliva of 20 mL was added to each well using the micropipette and was kept in the incubator at 37Â°C for 72 h. After 72 h, saliva was removed without touching the walls or the base of the wells. Each row was treated either with slurry prepared with Ganoderma/herbal/Colgate total toothpaste or herbal/chlorhexidine mouthwash/distilled water. One row of wells was kept as a control using erythrosine dye. After 30 s, all the wells were rinsed with distilled water. Erythrosine dye was added to all the wells, kept for 30 s, and rinsed with distilled water. The tissue culture plate was kept in the ELx800MS machine (ELISA reader) which was set at 540 nm, and the readings were obtained. Results: The results showed that G. lucidum toothpaste slurry reduced plaque than herbal and chlorhexidine mouthwash. However, there was no significant difference in plaque reduction between herbal and G. lucidum toothpaste slurries. Conclusion: The present study concluded that G. lucidum had better antiplaque efficacy than herbal toothpaste, herbal mouthwash, and chlorhexidine mouthwash.